(untitled) (Revista de Culturas y Literaturas Comparadas, 2021)
This paper is a comparative analysis of two of Julio Cortázar’s works. The aim is to show how certain representative elements in his work —the fantastic and the monstrous as well as confinement, escape, or Doppelgangër— are already present in his early texts, among which are the collection of short stories Bestiario and the novel El examen. Besides, we shall see how the conjunction of these elements and the oppressive context in which the stories develop not only bring the stories together but also insert them into the dystopic trend which characterized mid 20th century literature.